The Effect of Edu-IFA on Knowledge and Compliance with Fe Tablet Consumption in Pregnant Women in Makassar City - Zhagira, Tira; Catherine Jusuf, Elizabet; Usman, Andi Nilawati; Ahmad, Mardiana; Nontji, Werna; Arsyad, Aryadi; Intan Idiana Hassan (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Anemia in pregnancy is still a serious problem in Indonesia, with a prevalence of 48.9%. Iron supplementation is widely considered an important strategy to reduce the incidence. The aim of the study is to analyze the effect of educational videos on the knowledge and compliance of pregnant women with Fe tablet consumption and to compare the impact of knowledge and compliance with the consumption of Fe tablets on pregnant women between the intervention group and the control group. The methods used in this study were quasi-experimental with a nonequivalent control group design. Sampling by the exhaustive sampling technique consisted of 64 respondents, with the intervention group of 32 people and the control group of 32 people. This study was carried out at the Dahlia Health Center and the Pertiwi Health Center in Makassar City for 5 months, with an intervention of 90 tablets or 3 months. Data were analyzed using the Chi-Square, Wilcoxon, McNemar, and Mann-Whitney tests. The result shows the intervention group showed a 100.0% increase in knowledge and 59.4% in compliance, while the control group experienced a 90.6% increase in knowledge and 56.2% in compliance. The educational video on the importance of blood supplement tablets during pregnancy effectively increases knowledge and compliance with Fe tablet consumption in pregnant women, so it is hoped that health workers can use educational video media as an alternative method in counseling.